Determination of standard molar volume of 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide on titanium dioxide surface - Ye, Nannan; Dai, Zhengxing; Chen, Yifeng; Ji, Xiaoyan; Lu, Xiaohua (Frontiers in Chemistry, 2024)
The fluids near the solid substrate display different properties compared to the bulk fluids owing to the asymmetric interaction between the fluid and substrate; however, to the best of our knowledge, no work has been conducted to determine the interfacial properties of fluids experimentally. In this work, we combined a pycnometer with experimental measurements and data processing to determine the standard thermodynamic properties of interfacial fluids for the first time. In the study, 1-hexyl-3methylimidazolium bis(trifluoromethylsulfonyl)imide ([Hmim][NTf2]) and titanium dioxide (P25) were chosen as the probes to prove the concept. It was found that, with the combination of the Gay-Lussac pycnometer and the colligative law, together with selecting a suitable solvent, it is possible and reliable to determine the standard molar volume of the immobilized [Hmim][NTf2]. Compared to the bulk phase, the molar volumes of [Hmim][NTf2] on the P25 surface reduce by 20.8% to 23.7% at temperatures from 293.15 to 323.15 K, and the reduction degrees decrease with increasing temperatures. The newly determined standard thermodynamic data was used to obtain the model parameters of hybrid electrolyte perturbed-chain statistical associating fluid theory density functional theory (ePC-SAFT-DFT), and further predictions of the density of interfacial ionic liquids with different film thicknesses were proved to be reliable in comparison with the experiment results.